Preparation method of modified nano silicon powder wrapped by polymer
By coating polymer PVDF on nanosilicon powder and embedded energy-containing oxidant AP, nanocomposite metal powder is prepared by spray granulation method, the problem of insufficient combustion and ignition performance of nanosilicon powder is solved, and efficient combustion and large-scale production are achieved.
Patent Information
- Application Number
- CN202510003635.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-14
AI Technical Summary
The combustion and ignition performance of existing nano-silicon powder in propellants or pyrotechnic powder is insufficient, and it is easy to cause particle agglomeration and agglomeration, making it difficult to meet the needs of engineering applications.
Modified nanosilicon powder was coated with polymer PVDF, and energized energy-containing oxidant AP was embedded in the polymer solution, and shell-core nanocomposite metal powder was prepared by spray granulation.
The uniform dispersion and efficient combustion of nano-silicon powder are achieved, the combustion performance and ignition performance are improved, the agglomeration and agglomeration problems are solved, and the production scale and safety are improved.
Smart Images

Figure CN119613209A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite energetic materials, and in particular relates to a method for preparing polymer material-coated nano metal powder. Background Art
[0002] Nano silicon powder is widely used in propellant fuel and pyrotechnics because of its high combustion calorific value, low electrostatic sensitivity, good storage stability, and low production cost. However, the melting and boiling points of silicon are relatively high (T m , 1414℃; T p , 3265℃,), it is difficult to ignite. Although nano silicon powder has high activity and can improve combustion efficiency to a certain extent, it is easy to cause particle agglomeration and agglomeration. And as the particle size of silicon powder decreases, its ignition energy decreases exponentially.
[0003] Therefore, in order to give full play to the advantages of nano-silicon powder, achieve the excellent combustion performance of nano-silicon powder and improve the ignition performance and storage performance, it is urgent to solve the above-mentioned technical problems, so as to realize the full play of nano-silicon powder in propellants or pyrotechnics.
[0004] The document "Yan Qilong, Zuo Beilin et al. Preparation method of polymer-based composite energetic material coated modified nanometal particles (patent number: CN 110452075 A)" discloses a method for coating nanosilicon powder. The method uses an electrostatic spray method to add nanosilicon powder to a precursor polymer solution, and then embeds an energetic oxidant ammonium perchlorate (AP) or hexanitrohexaazaisopentane (CL-20) in the solution to form a zero-oxygen-balanced composite micro-nano material. The polymer material used is NC (nitrocellulose) or PVDF (polyvinylidene fluoride), and the final composites are Si@PVDF / CL-20 and Si@NC / AP. Although the particle size distribution of the composite is uniform, the particle sphericity is high, and it is not easy to agglomerate, the preparation method has a small yield and is only suitable for laboratory research and cannot meet engineering applications. In addition, studies have found that polymer NC is prone to aging during long-term storage. In addition, in the process of preparing Si@PVDF / CL-20 composites by electrostatic spraying, safety accidents are easily caused due to the high sensitivity of the oxidant CL-20. Summary of the invention
[0005] The present invention provides a method for preparing nano silicon powder modified by polymer encapsulation, which is characterized by comprising the following steps:
[0006] Step 1: dissolving the polymer PVDF in an organic solvent N-dimethylformamide DMF, adding Si powder after ultrasonic treatment, and then performing magnetic stirring to fully mix the nano metal powder and the polymer solution;
[0007] Step 2: Adding energetic oxidant AP to the polymer solution containing nano-Si powder, stirring magnetically, and then performing ultrasonic treatment to obtain a precursor solution PVDF / AP / Si;
[0008] Step 3: Set relevant parameters and adopt spray granulation method to prepare coated and modified shell-core nanocomposite metal powder.
[0009] In a specific embodiment of the present invention, the method for preparing modified nano silicon powder by polymer encapsulation specifically comprises the following process steps:
[0010] Step 1: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonically treat for 1 hour; Gently pour 600 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension;
[0011] Step 2: Doping of oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetically stirred for 2 hours, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution;
[0012] Step 3: Prepare silicon-based composite nanoparticles by spray granulation method. The process parameters are as follows: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 6 ml·min -1 , the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 60% are marked as Si-60%@PVDF / AP.
[0013] In another specific embodiment of the present invention, the method for preparing the modified nano silicon powder by polymer encapsulation specifically comprises the following process steps:
[0014] Step 1: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N, N-dimethylformamide (DMF) solvent and treat with ultrasound for 1 hour; Gently pour 327.3 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension;
[0015] Step 2: Doping of oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetic stirring for 2 hours, and ultrasonic treatment for 1 hour to obtain a PVDF / Si / AP precursor solution;
[0016] Step 3: Prepare silicon-based composite nanoparticles by spray granulation method. The process parameters are as follows: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 6 ml·min -1 , the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 45% are marked as Si-45%@PVDF / AP.
[0017] In another specific embodiment of the present invention, the method for preparing modified nano silicon powder by polymer encapsulation specifically comprises the following process steps:
[0018] Step 1: Coating of nano-silicon powder: 100 mg PVDF was dissolved in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonicated for 1 hour; 171 mg Si was gently poured into the PVDF solution three times and magnetically stirred for 2 hours to obtain a PVDF / Si suspension;
[0019] Step 2: doping with oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetic stirring for 2 hours, and ultrasonic treatment for 1 hour to obtain a PVDF / Si / AP precursor solution;
[0020] Step 3: Prepare silicon-based composite nanoparticles by spray granulation method. The process parameters are as follows: fan frequency 30 Hz, needle passing time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120℃; the composite particles Si@PVDF / AP with a silicon content of 30% are marked as Si-30%@NC / AP.
[0021] In another specific embodiment of the present invention, the method for preparing the modified nano silicon powder by polymer encapsulation specifically comprises the following process steps:
[0022] Step I: Coating of nano-silicon powder: 100 mg PVDF was dissolved in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonicated for 1 hour; 44.4 mg Si was gently poured into the PVDF solution three times and magnetically stirred for 2 hours to obtain a PVDF / Si suspension;
[0023] Step II: doping with oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetically stirred for 1 hour, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution;
[0024] Step III: Preparation of silicon-based composite nanoparticles by spray granulation, the process parameters are as follows: fan frequency 30 Hz, needle passing time 3 s, peristaltic speed 8 ml·min -1, the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 10% are marked as Si-10%@PVDF / AP.
[0025] In another specific embodiment of the present invention, the method for preparing the modified nano silicon powder by polymer encapsulation specifically comprises the following process steps:
[0026] Step A: Coating of nano-silicon powder: 100 mg PVDF was dissolved in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonically treated for 1 hour; 21 mg Si was gently poured into the PVDF solution three times and magnetically stirred for 2 hours to obtain a PVDF / Si suspension;
[0027] Step B: doping with oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetically stirred for 2 hours, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution;
[0028] Step C: Preparation of silicon-based composite nanoparticles by spray granulation, the process parameters are as follows: fan frequency 30 Hz, needle passing time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 5% are marked as Si-5%@PVDF / AP.
[0029] The present invention adopts a spray granulation method to add nano silicon powder to a precursor polymer solution, and then embeds an energetic oxidant AP in the solution to form a zero oxygen balance composite micro-nano material. The composite nano metal powder obtained by the spray granulation method has a uniform particle size distribution, a high particle sphericity, and is not easy to agglomerate. The polymer material used is PVDF, which is a high molecular polymer with excellent mechanical properties and is easily soluble in organic solvents. Therefore, the metal silicon powder can be effectively and evenly dispersed in the precursor solution. In addition, the energetic oxidant AP is added to the system. Through the spray granulation method, the problems of easy oxidation of existing nano silicon powder and low energy and ignition performance of nano powder coated by traditional methods can be solved.
[0030] The beneficial effects of the present invention are:
[0031] (1) The spray granulation method is used to prepare silicon-based composites, which can increase the production of silicon-based composites from a few grams to hundreds of kilograms.
[0032] (2) At present, AP (sodium perchlorate) is the most widely used energetic oxidant in the production of composite solid propellants (accounting for 60% to 70% of solid propellants) and is also the easiest oxidant to produce. Therefore, this oxidant is selected for coating nano-silicon powder. On the one hand, it can effectively reduce the coating cost. On the other hand, AP releases a large amount of oxygen during the combustion process, which can undergo redox reaction with silicon powder and improve the combustion efficiency of silicon powder.
[0033] (3) By rationally designing the optimal ratio of polymer PVDF, energetic oxidant AP and silicon powder, a zero oxygen equilibrium composite Si@PVDF / AP is obtained, thereby achieving the maximum energy release rate of the metal-based composite energetic material. In this formula design, the addition of silicon powder can not only react with PVDF, but also with AP. Therefore, compared with a single silicon powder, the superposition of the three components in the composite will obtain the most excellent energy performance and combustion performance.
[0034] (4) AP easily absorbs moisture and agglomerates at room temperature, which affects its performance. PVDF encapsulation can solve the problem of silicon powder agglomeration and the problem of AP easily absorbing moisture at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The morphology of the composite microspheres Si@PVDF / AP is shown, where the first row Figure 1 (a) Figure 1 (b) SEM images of the composite Si-30%@PVDF / AP at different magnifications; Figure 1 (c) shows the SEM image of the composite after EDS surface scanning; the second row shows the typical elements obtained by surface scanning from left to right, including F, O, Cl, and Si; the left figure in the third row shows the typical element N obtained by surface scanning; Figure 1 (d) represents the proportion of each element after surface scanning;
[0036] Figure 2 It is a composite Si / PVDF / AP prepared by mechanical mixing, wherein Figure 2 (a) and Figure 2 (b) SEM images of the morphological characteristics of the mechanical composite Si / PVDF / AP at magnifications of 100,000 times and 500,000 times, respectively;
[0037] Figure 3 The DSC curves of Si@PVDF / AP composite with 30% silicon content at different heating rates are shown. Figure 3 (a) shows a heating rate of 5°C min -1 The thermal weight loss process (TG curve) and thermal decomposition rate change process (DTG curve) of the composite Si@PVDF / AP. Figure 3(b) shows the heating rate of 10°C min -1 The thermal weight loss process (TG curve) and thermal decomposition rate change process (DTG curve) of the composite Si@PVDF / AP. Figure 3 (c) shows a heating rate of 15°C min -1 The thermal weight loss process (TG curve) and thermal decomposition rate change process (DTG curve) of the composite Si@PVDF / AP. Figure 3 (d) shows the heating rate of 20℃min -1 The thermal weight loss process (TG curve) and thermal decomposition rate change process (DTG curve) of the composite Si@PVDF / AP.
[0038] Figure 4 The TG-DTG curve of the mechanical composite Si / PVDF / AP is shown. Figure 4 (a) shows that the heating rate is 5℃min -1 The thermal weight loss process (TG curve) and thermal decomposition rate change process (DTG curve) of the composite Si / PVDF / AP when the heating rate is 10℃ min -1 The thermal weight loss process (TG curve) and thermal decomposition rate change process (DTG curve) of the composite Si / PVDF / AP. DETAILED DESCRIPTION
[0039] The present invention will be described in detail below with reference to the accompanying drawings.
[0040] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing modified nano-metal particles coated with polymer-based composite energetic materials, which is characterized by comprising the following steps:
[0041] Step 1: Dissolve the polymer PVDF in a suitable organic solvent N,N-dimethylformamide (DMF), add a certain proportion of Si powder (Si powder is added three times) after ultrasonic treatment for 1 hour, and then magnetically stir for 2 hours to fully mix the nanometal powder and the polymer solution.
[0042] Step 2: Add a certain proportion (PVDF / AP mass ratio 1:3) of energetic oxidant AP to the polymer solution containing nano-Si powder, stir magnetically for 2 hours, and ultrasonically treat for 1 hour to obtain a precursor solution PVDF / AP / Si.
[0043] Step 3: Set relevant parameters (fan frequency, needle passing time, peristaltic speed, fan heating temperature), and adopt spray granulation method to prepare coated and modified shell-core nanocomposite metal powder.
[0044] Example 1
[0045] The preparation method of polymer PVDF coated nano metal silicon powder particles comprises the following process steps:
[0046] Step 1: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonicate for 1 hour. Gently pour 600 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension.
[0047] Step 2: Doping of oxidant: Add 300 mg of energetic oxidant AP in a certain proportion (PVDF / AP mass ratio 1:3) to the PVDF / Si suspension solution, stir magnetically for 2 hours, and ultrasonically treat for 1 hour to obtain a PVDF / Si / AP precursor solution.
[0048] Step 3: Preparation of silicon-based composite nanoparticles by spray granulation: Spray granulation was performed using the following process parameters: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 6 ml·min -1 , the fan heating temperature is 120° C. The composite particles Si@PVDF / AP with a silicon content of 60% are marked as Si-60%@PVDF / AP.
[0049] Example 2
[0050] The preparation method of polymer PVDF coated nano metal silicon powder particles comprises the following process steps:
[0051] Step 1: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonicate for 1 hour. Gently pour 327.3 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension.
[0052] Step 2: Doping of oxidant: 300 mg of energetic oxidant AP was added to the PVDF / Si suspension solution in a certain proportion (PVDF / AP mass ratio 1:3), magnetically stirred for 2 hours, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution.
[0053] Step 3: Preparation of silicon-based composite nanoparticles by spray granulation: Spray granulation was performed using the following process parameters: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 6 ml·min -1 , the fan heating temperature is 120° C. The composite particles Si@PVDF / AP with a silicon content of 45% are marked as Si-45%@PVDF / AP.
[0054] Example 3
[0055] The preparation method of polymer PVDF coated nano metal silicon powder particles comprises the following process steps:
[0056] Step 1: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N,N-dimethylformamide (DMF) solvent and ultrasonicate for 1 hour. Gently pour 171 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension.
[0057] Step 2: doping of oxidant: 300 mg of energetic oxidant AP was added to the PVDF / Si suspension solution in a certain proportion (PVDF / AP mass ratio 1:3), magnetically stirred for 2 hours, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution.
[0058] Step 3: Preparation of silicon-based composite nanoparticles by spray granulation: Spray granulation was performed using the following process parameters: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120°C. The composite particles Si@PVDF / AP with a silicon content of 30% are marked as Si-30%@NC / AP.
[0059] Example 4
[0060] The preparation method of polymer PVDF coated nano metal silicon powder particles comprises the following process steps:
[0061] Step I: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N,N-dimethylformamide (DMF) solvent and ultrasonicate for 1 hour. Gently pour 44.4 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension.
[0062] Step II: doping of oxidant: 300 mg of energetic oxidant AP was added to the PVDF / Si suspension solution in a certain ratio (PVDF / AP mass ratio 1:3), magnetically stirred for 1 hour, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution.
[0063] Step III: Preparation of silicon-based composite nanoparticles by spray granulation: Spray granulation was performed using the following process parameters: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120° C. The composite particles Si@PVDF / AP with a silicon content of 10% are marked as Si-10%@PVDF / AP.
[0064] Example 5
[0065] The preparation method of polymer PVDF coated nano metal silicon powder particles comprises the following process steps:
[0066] Step A: Coating of nano-silicon powder: 100 mg PVDF was dissolved in 15 ml N,N-dimethylformamide (DMF) solvent and ultrasonicated for 1 hour. 21 mg Si was gently poured into the PVDF solution three times and magnetically stirred for 2 hours to obtain a PVDF / Si suspension.
[0067] Step B: doping of oxidant: 300 mg of energetic oxidant AP was added to the PVDF / Si suspension solution in a certain proportion (PVDF / AP mass ratio 1:3), magnetically stirred for 2 hours, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution.
[0068] Step C: Preparation of silicon-based composite nanoparticles by spray granulation: Spray granulation was performed using the following process parameters: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120° C. The composite particles Si@PVDF / AP with a silicon content of 5% are marked as Si-5%@PVDF / AP.
[0069] The present invention specifically adopts the spray granulation method to prepare silicon-based composites with different silicon contents, wherein the CEA software calculation finds that when the silicon content is 30%, the energy performance of the composite is optimal. The following are the morphological characteristics and thermal decomposition characteristics of the composite energetic material Si-30%@PVDF / AP when the silicon content is 30%.
[0070] Figure 1 The scanning electron microscope image and elemental analysis image of the polymer PVDF modified nano-metal silicon powder particles prepared in Examples 1-3 of the present invention are shown in FIG. Figure 1 (a) and Figure 1 (b) SEM images of the composite Si-30%@PVDF / AP at different magnifications. Figure 1 (c) is the SEM image of the composite after EDS surface scanning. The typical elements obtained by the surface scanning are F, O, Cl, Si, and N. Figure 1 (d) represents the proportion of each element after surface scanning.
[0071] Figure 2 It is a composite Si / PVDF / AP prepared by mechanical mixing, wherein Figure 2 (a) and Figure 2 (b) SEM images of the morphological characteristics of the mechanical composite Si / PVDF / AP at magnifications of 100,000 times and 500,000 times, respectively.
[0072] contrast Figure 1 and Figure 2 It can be seen that the composite prepared by spray granulation has better sphericity, while the internal particles of the composite prepared by mechanical mixing are randomly stacked and cannot form a composite with uniform components.
[0073] Figure 3 The thermal analysis curve of polymer PVDF coated nano-metal silicon powder particles prepared in Example 1-3. In order to illustrate that the composite Si@PVDF / AP prepared by spray granulation has better thermal stability than the composite Si / PVDF / AP prepared by mechanical mixing, the thermal decomposition properties of the composite materials Si@PVDF / AP and Si / PVDF / AP when the silicon content is 30% were studied respectively. Figure 3 and Figure 4 shown. Figure 3 The heating rate is 5℃ min -1 、10℃ min -1 、15℃ min -1 and 20℃ min -1 TG-DTG curve of Si@PVDF / AP composite, where Figure 3 (a) Heating rate 5℃ min -1 TG and DTG curves of the composite Si@PVDF / AP; Figure 3 (b) Heating rate: 10℃ min -1 TG and DTG curves of the composite Si@PVDF / AP; Figure 3 (c) Heating rate: 15℃min -1 TG and DTG curves of the composite Si@PVDF / AP; Figure 3 (d) Heating rate: 20℃ min -1 TG and DTG curves of the composite Si@PVDF / AP.
[0074] Depend on Figure 3 It can be seen from the TG curve that with the increase of the heating rate, the thermal decomposition of the composite gradually changes from two platforms to one platform, and the DTG curve shows an obvious sharp peak, indicating that the composite Si@PVDF / AP undergoes a self-catalytic reaction.
[0075] Figure 4 The heating rate is 5℃ min -1 and 10℃ min -1 TG-DTG curve of mechanical composite Si / PVDF / AP with 30% silicon content, where Figure 4 (a) indicates a heating rate of 5°C min -1 TG-DTG curve of the complex. Figure 4 (b) indicates a heating rate of 10°C min -1TG-DTG curve of the complex.
[0076] Depend on Figure 4 It can be seen that the heating rate is 5℃ min -1 and 10℃ min -1 When the composite Si / PVDF / AP was ignited, a runaway reaction occurred (a sharp peak appeared on the DTG curve). Figure 3 It can be seen that at the same heating rate, the composite Si@PVDF / AP did not experience ignition runaway reaction. Figure 3 and Figure 4 It can be seen that the mechanical composite Si / PVDF / AP underwent an ignition runaway reaction at a lower heating rate, indicating that its thermal stability is poorer than that of the composite Si@PVDF / AP.
[0077] Table 1 describes the differences in electrostatic sensitivity and impact sensitivity of the silicon-based composites Si@PVDF / AP and Si / PVDF / AP.
[0078] Table 1 Sensitivity test of silicon-based composites Si-30@PVDF / AP and Si-30 / PVDF / AP
[0079]
[0080] As can be seen from Table 1, the impact sensitivity of the silicon-based composite Si@PVDF / AP is significantly lower than that of the mechanical mixture Si / PVDF / AP. The friction sensitivity of the silicon-based composite Si@PVDF / AP is significantly lower than that of the mechanical mixture Si / PVDF / AP. This indicates that the thermal stability of the silicon-based composite Si@PVDF / AP prepared by spray granulation is better than that of the mechanical mixture Si / PVDF / AP.
[0081] In summary, in order to increase the yield of the silicon-based composite and increase the energy and combustion performance of the composite, the present invention adopts a spray granulation method to prepare a new silicon-based composite Si@PVDF / AP. The spray granulation method can continuously produce a few grams to hundreds of kilograms of composites. Since AP (sodium perchlorate) is currently the most used energetic oxidant in the production of composite solid propellants, it is also the easiest oxidant to produce. Therefore, the relative patent of this invention (patent number: CN 110452075A) effectively reduces the cost of coating silicon powder. In addition, the optimal ratio of PVDF, AP and silicon powder is wrapped, so that the energy release efficiency of the composite Si@PVDF / AP is maximized.
Claims
1. A method for preparing nano silicon powder modified by polymer encapsulation, characterized in that: The specific steps include: Step 1: dissolving the polymer PVDF in an organic solvent N-dimethylformamide DMF, adding Si powder after ultrasonic treatment, and then performing magnetic stirring to fully mix the nano metal powder and the polymer solution; Step 2: Adding energetic oxidant AP to the polymer solution containing nano-Si powder, stirring magnetically, and then performing ultrasonic treatment to obtain a precursor solution PVDF / AP / Si; Step 3: Set relevant parameters and adopt spray granulation method to prepare coated and modified shell-core nanocomposite metal powder.
2. The method for preparing modified nano silicon powder by polymer encapsulation according to claim 1, characterized in that: The specific process steps include: Step 1: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N, N-dimethylformamide (DMF) solvent and treat with ultrasound for 1 hour; Gently pour 600 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension; Step 2: Doping of oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetically stirred for 2 hours, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution; Step 3: Prepare silicon-based composite nanoparticles by spray granulation method. The process parameters are as follows: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 6 ml·min -1 , the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 60% are marked as Si-60%@PVDF / AP.
3. The method for preparing modified nano silicon powder by polymer encapsulation according to claim 1, characterized in that: The specific process steps include: Step 1: Coating of nano-silicon powder: Dissolve 100 mg PVDF in 15 ml N, N-dimethylformamide (DMF) solvent and treat with ultrasound for 1 hour; Gently pour 327.3 mg Si into the PVDF solution three times and stir magnetically for 2 hours to obtain a PVDF / Si suspension; Step 2: Doping of oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetic stirring for 2 hours, and ultrasonic treatment for 1 hour to obtain a PVDF / Si / AP precursor solution; Step 3: Prepare silicon-based composite nanoparticles by spray granulation method. The process parameters are as follows: fan frequency 30 Hz, needle passage time 3 s, peristaltic speed 6 ml·min -1 , the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 45% are marked as Si-45%@PVDF / AP.
4. The method for preparing modified nano silicon powder by polymer encapsulation according to claim 1, characterized in that: The specific process steps include: Step 1: Coating of nano-silicon powder: 100 mg PVDF was dissolved in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonically treated for 1 hour; 171 mg Si was gently poured into the PVDF solution three times and magnetically stirred for 2 hours to obtain a PVDF / Si suspension; Step 2: doping with oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetic stirring for 2 hours, and ultrasonic treatment for 1 hour to obtain a PVDF / Si / AP precursor solution; Step 3: Prepare silicon-based composite nanoparticles by spray granulation method. The process parameters are as follows: fan frequency 30 Hz, needle passing time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120℃; the composite particles Si@PVDF / AP with a silicon content of 30% are marked as Si-30%@NC / AP.
5. The method for preparing modified nano silicon powder by polymer encapsulation according to claim 1, characterized in that: The specific process steps include: Step I: Coating of nano-silicon powder: 100 mg of PVDF was dissolved in 15 ml of N,N-dimethylformamide (DMF) solvent and ultrasonically treated for 1 hour; 44.4 mg of Si was gently poured into the PVDF solution three times and magnetically stirred for 2 hours to obtain a PVDF / Si suspension; Step II: doping with oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetically stirred for 1 hour, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution; Step III: Preparation of silicon-based composite nanoparticles by spray granulation, the process parameters are as follows: fan frequency 30 Hz, needle passing time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 10% are marked as Si-10%@PVDF / AP.
6. The method for preparing modified nano silicon powder by polymer encapsulation according to claim 1, characterized in that: The specific process steps include: Step A: Coating of nano-silicon powder: 100 mg PVDF was dissolved in 15 ml N, N-dimethylformamide (DMF) solvent and ultrasonically treated for 1 hour; 21 mg Si was gently poured into the PVDF solution three times and magnetically stirred for 2 hours to obtain a PVDF / Si suspension; Step B: doping with oxidant: 300 mg of energetic oxidant AP was added to the suspension solution of PVDF / Si, with a PVDF / AP mass ratio of 1:3, magnetically stirred for 2 hours, and ultrasonically treated for 1 hour to obtain a PVDF / Si / AP precursor solution; Step C: Preparation of silicon-based composite nanoparticles by spray granulation, the process parameters are as follows: fan frequency 30 Hz, needle passing time 3 s, peristaltic speed 8 ml·min -1 , the fan heating temperature is 120°C; the composite particles Si@PVDF / AP with a silicon content of 5% are marked as Si-5%@PVDF / AP.
Citation Information
Patent Citations
Preparation method of polymer-based composite energetic material-coated modified nano metal particles
CN110452075A
Cited By
High-temperature-resistant composite ceramic material and preparation method thereof
CN120229949A